Beyond the Sublime: The Aesthetics of the Analogy of Being (part Two) - Betz, John (Modern theology, 2006)
This essay, the second half of a larger work, offers a constructive proposal for a theological aesthetics based upon a theological ontology of the analogia entis. The doctrine of the analogia entis, as articulated most famously by Erich Przywara, S. J., has been the subject of much criticism; however, the essay attempts to defend the doctrine, specifically, against the criticisms of Karl Barth and Martin Heidegger. The essay then offers a précis of Przywara's actual doctrine—beyond typical characterizations of it—with a view to the possibility it offers for a theological aesthetics and, specifically, for a genuinely theological account of the relationship between the beautiful and the sublime.